Isolation and identification of berberine and berberrubine metabolites by berberine-utilizing bacterium Rhodococcus sp. strain BD7100. Issue 5 (3rd May 2016) - Ishikawa, Kazuki; Takeda, Hisashi; Wakana, Daigo; Sato, Fumihiko; Hosoe, Tomoo
Abstract: Based on the finding of a novel berberine (BBR)-utilizing bacterium, Rhodococcus sp. strain BD7100, we investigated the degradation of BBR and its analog berberrubine (BRU). Resting cells of BD7100 demethylenated BBR and BRU, yielding benzeneacetic acid analogs. Isolation of benzeneacetic acid analogs suggested that BD7100 degraded the isoquinoline ring of the protoberberine skeleton. This work represents the first report of cleavage of protoberberine skeleton by a microorganism. Graphical abstract: : BBR-utilizing bacterium, Rhodococcus sp. BD7100 demethylenated BBR and BRU, yielding benzeneacetic acid analogs in which their protoberberine skeletons were cleaved.